The loss of helical flow in the thoracic aorta might be an identifying marker for the risk of acute type B aortic dissection. (March 2023) - Li, Da; Wang, Jiarong; Zeng, Wen; Zeng, Xiangguo; Liu, Zhan; Cao, Haoyao; Yuan, Ding; Zheng, Tinghui
Highlights: This case-control hemodynamic study suggested that. The obvious helical flow was found in healthy aortic arches. The loss of helical flow and increased NtransWSS were observed in pre-TBAD subjects, which might result in abnormal flow disturbance and increased risk of dissection. With the help of 4D flow MRI, clinicians could capture changes in helical flow features in the thoracic aorta to stratify risk of potential TBAD, especially in patients with a history of hypertension, abnormal arch morphology, and genetic defects. Abstract: Background and Objective: The occurrence of acute type B aortic dissection (TBAD) remained unclear. This study aimed to investigate the association between flow features and hemodynamic parameters in aortas that demonstrated the risk of TBAD occurrence. Methods: The geometries of 15 hyperacute TBAD and 12 control patients (with healthy aorta) were reconstructed from computed tomography angiography images. Pre-TBAD models were then obtained by eliminating the dissection flaps. Flow features and hemodynamic parameters, including wall shear stress-related parameters and helicities, were compared between pre-TBAD and control models using computational fluid dynamics. Results: There were no significant differences in baseline characteristics and anatomical parameters between the two groups. Significant contralateral helical blood flow was present in the healthy thoracic aorta, while almost no helical flow was observed in the pre-TBAD group. In addition, the mean normal transverse wall shear stress (NtransWSS) was significantly higher in the pre-TBAD group (aortic arch 0.49±0.09 vs. 0.40±0.05, P = 0.04; descending aorta: 0.46±0.05 vs. 0.33±0.02, P <0.01). Moreover, a significantly negative correlation was found between helicity and NtransWSS in the descending aorta. Moreover, the location of primary tears in 12 pre-TABD subjects matched well with regions of high NtransWSS. Conclusions: Loss of helical flow in the aortic arch and descending aorta may be a major flow feature in patients with underlying TBAD, resulting in increased flow disturbance and wall lesions.